The Efficacy of Medial Patellofemoral Ligament Reconstruction Combined with Tibial Tuberosity Transfer in the Treatment of Patellofemoral Instability - Boutefnouchet, Tarek (Knee Surg Relat Res, 2016)
A systematic review of the literature was undertaken to evaluate the efficacy of medial patellofemoral ligament (MPFL) reconstruction combined with tibial tuberosity transfer (TTT) in the treatment of patellofemoral instability. Using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic search was carried out to identify and review the published literature pertinent to MFPL reconstruction combined with TTT. Relevant studies were critically appraised with narrative data synthesis. Studies that met the eligibility criteria were suitable for appraisal and consisted of case series and therapeutic series (levels IV & III). All studies had inherent variations in outcomes reporting and limited follow-up. Combined treatment offers restoration of normal anatomy, thus adding clinical value to the currently recommended anatomic approach to MPFL reconstruction. Nevertheless, the current body of evidence does not determine the threshold at which patellofemoral axis requires the need for adjunctive distal realignment as opposed to MPFL reconstruction alone. This review highlighted numerous recurring limitations in the conduct and presentation of the studies, which inadvertently mitigated the interpretation of their results. Future priority should be awarded to larger randomised controlled trials utilising validated patient reported outcome measures.